Kedudukan Hukum Kepemilikan Saham Yang Diperoleh Dari Hasil Saham Bonus Terhadap Harta Bersama - Irsyadilla Hafizh Heru Sadjarwo (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2021)
This paper focuses on the topic of What is the Legal Position of Bonus Shares in a Company Legal Perspective? What is the Legal Position of Bonus Shares Against Mixing of Marriage Assets? The method used in this paper is a normative juridical approach, using a statutory approach approach (postproach status), conceptual approach (conceptual approach) and case approach. The results of this study indicate that the legal position of Bonus Shares in the perspective of Company Law is as dividends and if it is related to marital assets, then from the perspective of marriage law, Bonus Shares can become Congenital Assets or Joint Assets depending on the time of acquisition. The conclusion of this research is that if it is related to marital assets, the position of Bonus Shares in marital assets needs to be reviewed from the time the Bonus Shares are acquired. If the Bonus Shares are obtained during the marriage, the Bonus Shares will become joint assets even though the original shares were acquired either before marriage or at the time of marriage as regulated in Article 35 paragraph (1) of Law Number 1 of 1974 concerning Marriage. Meanwhile, if the Bonus Shares are obtained prior to the marriage, even though the party concerned carries out the marriage, the Bonus Shares remain the assets concerned as stipulated in Article 35 paragraph (2) of Law Number 1 of 1974 concerning Marriage.